PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 56 BALAI MAKAM KECAMATAN MANDAU KABUPATEN BENGKALIS - Syafridawati '; Mahmud Alpusari; Zariul Antosa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Based on the background of the problems in science learning in class IV SD Negeri 56 Balai Makam Mandau sub Bengkalis still far from the expectations and objectives to be achieved, because the learning is still Verbalitas. Teachers still as a learning center and often use the lecture method. Students are still less active and less passion, less attention in learning when the teacher explains, quickly get bored and talking with your seatmate. Students are less able to associate lessons learned with lessons to be learned. And things like that happen it causes the student's knowledge does not develop, the skills are not trained and students are not accustomed to solve its problems alone. Subjects in this study is the teacher and the fourth grade students of SD Negeri 56 Balai Makam Saber Duri Bengkalis District of the 2015/2016 school year totaling 28 students .. In addition, the researchers used a type of classroom action research conducted in two cycles during 4 meetings. Each cycle is carried out through four stages, namely planning, action, observation, and reflection. The data collection technique is carried out through tests, observations, and documentation. The results of the average value of the basic score is 60.71 students increased to 78.21 at the end of the cycle I. replay at end of cycle II replicates increased again to 83.04. Mastery learning in the first cycle and increased 75% in Cycle II with 92.9%. Key Words: STAD, learning outcomes IPA